Design of an automatic sprinkler irrigation system for the Welsh onion growing, in La Puerta farm (Tota-Boyacá) (2012)
This paper presents the design for automating sprinkler irrigation system in a Welsh onion growing, which poses the required parameters, establishes the differences, advantages and results related to the traditional irrigation system used in this region (Tota, Boyacá). Starting from the resources owned by the farming unit, calculations of water requests of the plant, taking into account the crop evapotranspiration, the irrigation planning with certain factors on the basis of effective storage of soils. Two different technologies for the design are presented: hard-wired and programmable logic. The hard-wired logic system is developed as an automatic cyclical sequence with four work timed stages; on the other hand, the programmable logic controller PLC used, is the Easy-512-DC of Moller, which is provided with eight digital inputs and four relay outputs, programmed in Ladder according to the sequence of the process.